Micronutrient deficiency and treatment adherence in a randomized controlled trial of micronutrient supplementation in ART-naïve persons with HIV. - Louise Balfour; Johanna N Spaans; Dean Fergusson; Harold Huff; Edward J Mills; Charles J la Porte; Sharon Walmsley; Neera Singhal; Ron Rosenes; Nancy Tremblay; M John Gill; Hugues Loemba; et al. (PLoS ONE)
Introduction The MAINTAIN study is an on-going RCT comparing high-dose micronutrient and anti-oxidant supplementation versus recommended daily allowance (RDA) vitamins in slowing HIV immune deficiency progression in ART-naïve people with HIV infection. Objective We planned analysis of the first 127 participants to determine the baseline prevalence of serum micronutrient deficiencies and correlates, as well as tolerance and adherence to study interventions. Methods Participants receive eight capsules twice daily of 1) high-dose or 2) RDA supplements for two years and are followed-up quarterly for measures of immune deficiency progression, safety and tolerability. Regression analysis was used to identify correlates of micronutrient levels at baseline. Adherence was measured by residual pill count, self-report using the General Treatment Scale (GTS) and short-term recall HIV Adherence Treatment Scale (HATS). Results Prior micronutrient supplementation (within 30 days) was 27% at screening and 10% of study population, and was not correlated with baseline micronutrient levels. Low levels were frequent for carotene (24%<1 nmol/L), vitamin D (24%<40 nmol/L) and serum folate (20%<15 nmol/L). The proportion with B12 deficiency (<133 pmol/L) was 2.4%. Lower baseline levels of B12 correlated lower baseline CD4 count (r = 0.21, p = 0.02) with a 21 pmol/L reduction in B12 per 100 cells/µL CD4. Vitamin D levels were higher in men (p<0.001). After a median follow-up of 1.63 years, there were 19 (15%) early withdrawals from the study treatment. Mean treatment adherence using pill count was 88%. Subjective adherence by the GTS was 81% and was moderately but significantly correlated with pill count (r = 0.29, p<0.001). Adherence based on short-term recall (HATS) was >80% in 75% of participants. Conclusion Micronutrient levels in asymptomatic HIV+ persons are in keeping with population norms, but micronutrient deficiencies are frequent. Adherence levels are high, and will permit a valid evaluation of treatment effects. Trial registration ClinicalTrials.gov NCT00798772.